Genetic polymorphisms in candidate genes are not associated with increased vincristine-related peripheral neuropathy in Arab children treated for acute childhood leukemia: a single institution study. Issue 8 (August 2018) - Zgheib, Nathalie K.; Ghanem, Khaled M.; Tamim, Hani; Aridi, Carole; Shahine, Randa; Tarek, Nidale; Saab, Raya; Abboud, Miguel R.; El-Solh, Hassan; Muwakkit, Samar A.
Abstract : Objective: The aim of this study was to evaluate the potential association between candidate genetic polymorphisms and vincristine-related peripheral neuropathy in Arab children with acute lymphoblastic leukemia (ALL). Patients and methods: This is a retrospective evaluation of 133 Arab children treated for ALL at the Children's Cancer Center of Lebanon. Incidence and severity of, as well as the timing (in weeks) at which grade 2 or higher peripheral neuropathy occurred were recorded. Genotyping for ABCB1 ( rs1045642 ), ABCB1 ( rs1128503 ), ABCC2 ( rs717620 ), CEP72 ( rs924607 ), ETAA1 ( rs17032980 ), and MTNR1B ( rs12786200 ) was performed. Results: A total of 26 (19.5%) individuals developed peripheral neuropathy, three of which occurred during the induction phase. No statistically significant associations were revealed for any of the polymorphisms with either incidence of vincristine-related toxicity, toxicity severity, or time to the first episode of grade 2 or higher vincristine-related peripheral neuropathy. Conclusion: This study presents the first pharmacogenetic analysis of vincristine-related peripheral neuropathy in children with ALL in an Arab country. We have shown that genetic polymorphisms in candidate genes are not associated with peripheral neuropathy secondary to chronic therapy with high-dose vincristine (2 mg/m 2 ) during the continuation phase. Concerning CEP72, our results are in line with the findings from the St Jude cohort of children treated for ALL with higher vincristine doses during chronic treatment. Larger high-throughput genetic analyses may be warranted to evaluate variants in other candidate genes such as CYP3A5 and reveal new nonpreviously reported alleles that may be peculiar to this region of the world. Abstract : Supplemental Digital Content is available in the text.